The Role of the Credit Services Market in Ensuring Stability of the Banking System - Zhavoronok, А.; Shchur, R.; Zhezherun, Yu.; Sadchykova, I.; Viadrova, N.; Tychkovska, L. (International Journal of Safety and Security Engineering, 2022)
In the article, the role of the credit services market in ensuring stability of the banking system is examined. The study was carried out on the basis of a detailed comparative analysis of the development of the banking system and the credit services market of Ukraine. This approach made it possible to identify the main prerequisites for the development of such a market, and possible options for the formation of crisis phenomena in its functioning. Within the article, it is also described in detail how the credit services market can have a destructive effect on stability of the country's banking system and its financial system. For this, considerable attention is paid to the description of the economic and political environment in which commercial banks have operated in Ukraine during the last twenty years. This made it possible to specify the causes of crisis situations in the country's banking system, justify the actions of state authorities in countering the consequences of such crises. The analysis of the financial stress index as an indicator of stability of the financial system functioning made it possible to establish the cyclic nature of its changes, which proved permanent emergence of crisis situations in the development of both the credit services market and the banking system of Ukraine.
Keywords: credit services market, national economy, banking system, banking institutions, stability of the banking system